Teen female risky sexual behavior: risk and protective factors - Hamsan, Hanina Halimatusaadiah; Abdullah, Haslinda; Ibrahim, Mohammad Zaki; Md Noor, Amna; Redzuan, Ma'rof (Universiti Putra Malaysia, 2012)
Teenage and unsafe sex behavior is the serious issue in many developing countries. This cross-sectional survey designed to identify the role of psychological maladjustment, family, peer, and school in risky sexual behavior among rural female adolescents in Peninsular Malaysia. A sample of 770 subjects, aged 13 – 17 from ten states in Malaysia participated in the study. The results indicate that 3.2% (n = 25) reported having had sexual intercourse. Among these 25 sexually active females, 64.0% (n = 16) stated that their first-time sex experience was at age 15 or younger, 20.0% (n=5) had multiple sex partners, 72.0% (n=18) no contraceptive use during last sex, and 12.0% (n=3) had experienced on unwanted pregnancy. Descriptive analysis also shows about 32.0% sexual experienced female adolescent come from imperfect family due to divorced/separated parents or father/mother/both parents died. Bivariate regression analysis indicates that negative attitude towards SRH, incomplete family structure, peers whose get involved in sexual disorder, lack of family communication and lack of school attachment were more likely to engage in sexually risky behaviors. Female adolescents who have positive attitude towards SRH, good family communication, completed family structure, and practice a healthy lifestyle with not involved in midnight activities are less likely to engage in sexually risky behaviors.